Comparison of two different techniques used for thyroidectomies; Conventional thyroidectomy vs. LigaSure - Sarwat Bibi; Summara Tabbasam; Sultan Mahmood Khan; Khurram Saqib; Muhammad Hamza Rana; Ifra Irfan (Journal of University Medical & Dental College, 2023)
BACKGROUND & OBJECTIVES: Certain interventions have been carried out to reduce blood loss during thyroidectomy to a great extent. The study aims to compare the efficacy of LigaSure thyroidectomy with conventional thyroidectomy. METHODOLOGY: A quasi experimental study was conducted at Aziz Fatimah Hospital, Faisalabad, and 58 patients were divided into two groups. Group A underwent conventional thyroidectomy and Group B LigaSure thyroidectomy. Preoperative and postoperative variables were recorded and analyzed in SPSS 21. An Independent t-test was used to compare the mean difference between the two groups. A p-value less than 0.05 was considered statistically significant. RESULTS: A total of 58 patients were enrolled in the study and divided into two groups. The mean age of patients in group A undergoing conventional thyroidectomy was (43.1±9.23) and in group B was (41.23±9.23) with p-value=0.4419 (non significant result was found among the age groups) . Mean operative time calculated for LigaSure-assisted hemithyroidectomy (28.57±3.45) minutes , subtotal thyroidectomy (43.33±2.86) minutes, and total thyroidectomy (73.15±9) minutes were significantly lower than those undergoing conventional thyroidectomies 40.12±6.5 minutes , 66.25±6.29 minutes , 87.35±7.02 minutes respectively. The mean difference in mean operative time and number of sutures used in both techniques were statistically significant p 0.05. CONCLUSION: Less mean operative time and suture ligations have increased the surgeon’s compliance toward the device. These devices are now the first choice for physicians and surgeons for thyroidectomies not only in Pakistan but also across the globe.